Gait analysis of male professional boxers - Jacek PERLIŃSKI; Joanna M. BUKOWSKA; Łukasz RYDZIK; Wojciech WĄSACZ; Dariusz KRUCZKOWSKI; Tadeusz AMBROŻY; Wojciech CZARNY; Jarosław JASZCZUR-NOWICKI (Baltic Journal of Health and Physical Activity)
Introduction: Gait plays a crucial role in both daily life and sports performance. This study analyzes professional boxers’ gait, as it is essential to understand its influence on performance and injury risk. However, there is a need to comprehend the effects of boxing training on gait and the occurrence of asymmetries between limbs. Research Question: Does the gait of professional boxers exhibit significant differences between limbs, and what are the potential implications of this asymmetry? Materials and Methods: The study involved 36 professional boxers, and the Gaitway 3D Pressure treadmill was used to collect data. The analysis was performed using statistical tests with a pre-determined level of significance. Results: Significant differences were found between limbs in gait phase parameters and ground reaction forces. A longer swing phase of the right leg was observed, potentially affecting the reduction of single-limb support and right-leg propulsion. Additionally, higher ground reaction forces were noted on the left side. Conclusions: This analysis of gait in professional boxers provides valuable insights into the asymmetry between limbs, which may impact performance and injury risk. It also shows the correct characteristics of selected gait parameters. These findings are relevant for tailoring training programs, reducing injuries, and enhancing overall physical conditioning of athletes. Further-more, they can be applied in both sports and daily life for injury prevention and rehabilitation, where maintaining balance and stability are crucial in avoiding injuries and improving the quality of life.